1997
DOI: 10.2169/internalmedicine.36.794
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Continuous Intravenous Infusion of Prostacyclin for Severe Primary Pulmonary Hypertension.

Abstract: patient suffering from severe symptomatic primary pulmonary hypertension (PPH) underwent long-term intravenous prostacyclin therapy; the first time for such treatment in Japan. A 26-year-old male had experienced gradually progressive dyspnea for about one year. Despite conventional therapy he suffered repeated syncopal attacks. However, after receiving a permanent central venous access device and a portable infusion pump, he recovered fully and was discharged. This remedy seems to be promising for PPHas has al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…If no desirable effect is obtained with these medications, we have to consider continuous intravenous infusion of the PGI 2 derivative sodium epoprostenol. 7,8) Meanwhile, a dual endothelin receptor antagonist, bosentan, has been available in Japan since 2005. 9) We report a case of IPAH in which repetitive syncope was successfully treated by bosentan.…”
mentioning
confidence: 99%
“…If no desirable effect is obtained with these medications, we have to consider continuous intravenous infusion of the PGI 2 derivative sodium epoprostenol. 7,8) Meanwhile, a dual endothelin receptor antagonist, bosentan, has been available in Japan since 2005. 9) We report a case of IPAH in which repetitive syncope was successfully treated by bosentan.…”
mentioning
confidence: 99%
“…This condition predominantly affects females in the third decade of life, and has a mean survival of less than three years from the time of diagnosis (15,16). At present, few satisfactory long-term treatment options other than lung transplantation (17,18) are available; and the principal therapy, continuous intravenous infusion of prostacyclin derivatives (19)(20)(21)(22), is associated with significant morbidity (22)(23)(24). The underlying etiology of PPH remains unclear, however several groups have suggested that endothelial dysfunction associated with a decrease in expression or biologic activity of the vasodilator nitric oxide synthase (NOS), either alone or in combination with the overexpression of the potent vasoconstrictor endothelin (25)(26)(27)(28)(29)(30)(31)(32)(33), plays a critical role.…”
mentioning
confidence: 99%